OPTIMIZATION OF PENSTOCK GEOMETRIC DESIGN ON HYDROPOWER SYSTEM - Triwibowo, Hari
Penstock is an important component in hydropower system. The function of this component is to accommodate the water flow from the forebay to the turbine. The existences of penstock allow for increased flow rate is influenced by the geometric size of the pipe. Increased speed is sparking potential for additional pressure (water hammer). In addition, the pipe going to the various forms of stress affect its structural stability. The main factors to be considered in penstocks geometric design is the size of the pipe, such as diameter, thickness, and length of the pipe. The values of this variable depend on the flow rate, head, and loss of energy. To get the right design, the principle of optimization must be applied toward technical and financial aspects. Optimization method used to apply analytical and empirical formulas. Empirical approach is done by applying Sarkaria and Fahlbusch equations in order to obtain the optimal size of the pipe diameter. As a comparison, an analytical approach is required to calculate the geometric size of the penstocks. Review the financial aspects focused on the amount of investment toward penstocks needed. Based on the calculation process, the obtained graph can be implemented as a method for determining the diameter of penstock in order to optimize the geometric design. Keywords: